2018
DOI: 10.1016/j.arthro.2018.03.037
|View full text |Cite
|
Sign up to set email alerts
|

Editorial Commentary: Hip Radiographic Measurement: It Takes More Than One

Karen Kay Briggs

Abstract: The success of hip arthroscopy is based on selecting the right patient. Radiographic measurements are commonly used in the diagnosis of femoroacetabular impingement and other hip pathologies that are treated with hip arthroscopy. Unfortunately, there is not one measurement. For proper patient selection, it is critical to assess for dysplasia and the level of osteoarthritis. The final diagnosis and the decision to proceed with hip arthroscopy should be based on a global evaluation of the joint using different r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…In 707 patients undergoing hip arthroscopic surgery for FAIS, Lansdown et al 16 suggested that the preoperative anteroposterior alpha angle, preoperative false profile alpha angle, and postoperative false profile alpha angle are the strongest predictors of outcomes in anterolateral-based cam lesions. However, Briggs 5 described the need for more than 1 radiographic parameter and view to evaluate the joint, particularly in the context of mild dysplasia. Fabricant et al 9 evaluated 243 patients who underwent arthroscopic surgery for FAIS and found that less significant clinical improvement occurred in the setting of relative femoral retroversion (<5° femoral anteversion); moreover, no association was found between the McKibbin index and PROM scores.…”
mentioning
confidence: 99%
“…In 707 patients undergoing hip arthroscopic surgery for FAIS, Lansdown et al 16 suggested that the preoperative anteroposterior alpha angle, preoperative false profile alpha angle, and postoperative false profile alpha angle are the strongest predictors of outcomes in anterolateral-based cam lesions. However, Briggs 5 described the need for more than 1 radiographic parameter and view to evaluate the joint, particularly in the context of mild dysplasia. Fabricant et al 9 evaluated 243 patients who underwent arthroscopic surgery for FAIS and found that less significant clinical improvement occurred in the setting of relative femoral retroversion (<5° femoral anteversion); moreover, no association was found between the McKibbin index and PROM scores.…”
mentioning
confidence: 99%